THE TRANSFORMATION OF CORPORATE STRUCTURES IN THE FORMATION OF A MODERN MARKET ECONOMY OF UKRAINE - Bobyl, V. V. (Science and Transport Progress, 2009)
In the paper the economic category «corporation» is considered, its economic-social characteristic in the conditions of establishment of the modern market economy ofUkraineis given.